INSOLVENCY WITHOUT BANKRUPTCY: Rethinking The Dissolution of Viable State-Owned Banks - Dewantara, Reka; Parikesit, I Gusti Ngurah (Jurisdictie: Jurnal Hukum dan Syariah, 2025)
This article examines the normative inconsistency between the Bankruptcy and Suspension of Debt Payment Obligations Law (UUK–PKPU) and the Company Law (UU PT), which creates a risk of premature dissolution of state-owned banks that are still economically viable. The study aims to conduct an epistemological and normative analysis of the bankruptcy regime applicable to state-owned banks in Indonesia by examining insolvency tests through a comparative law perspective and elaborating the concept of epistemic failure within the framework of Lon Fuller’s legal philosophy. This research employs a normative juridical method, using statutory, conceptual, and comparative approaches. Legal norms and principles are analysed through hermeneutic interpretation to assess their coherence and practical implications. The findings reveal that Indonesia’s current bankruptcy framework fails to distinguish clearly, both conceptually and operationally, between balance-sheet insolvency and cash-flow insolvency. As a result, banks experiencing temporary liquidity problems may be treated as insolvent, leading to premature liquidation despite their underlying economic soundness. This condition highlights a significant normative inconsistency between the UUK–PKPU and the Company Law. Furthermore, Indonesian bankruptcy law remains predominantly liquidation-oriented and relies heavily on procedural formalism. This approach contrasts with the legal frameworks of the European Union and common law jurisdictions, which prioritise rescue and rehabilitation mechanisms as primary responses to financial distress. Accordingly, this article strengthens the argument for regulatory harmonisation and advocates the adoption of a dual insolvency test, as well as the institutionalisation of rescue and rehabilitation mechanisms as mandatory priorities before liquidation in Indonesia’s bankruptcy law. Artikel ini menganalisis adannya inkonsistensi normatif antara Undang-Undang Kepailitan dan Penundaan Kewajiban Pembayaran Utang (UUK-PKPU) dan Undang-Undang Perseroan Terbatas (UU PT) yang berpotensi menimbulkan pembubaran prematur bank yang secara ekonomi masih layak. Tujuan penelitian adalah melakukan pendekatan epistemologis dan normatif terhadap regulasi kepailitan Bank BUMN di Indonesia, melalui analisis uji insolvabilitas dengan pendekatan hukum perbandingan, serta memperdalam konsep epistemic failure menggunakan kerangka filosofi hukum Lon Fuller. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan perundang-undangan, konseptual, dan komparatif, di mana norma dan prinsip hukum dianalisis melalui metode interpretasi hermeneutik. Hasil penelitian menunjukkan bahwa kerangka regulasi kepailitan di Indonesia saat ini gagal membedakan secara konseptual dan operasional antara insolvabilitas neraca dan insolvabilitas arus kas. Kegagalan tersebut mengakibatkan pembubaran prematur terhadap bank-bank BUMN yang sejatinya masih sehat secara ekonomi, serta mempertegas inkonsistensi normatif antara UUK-PKPU dan UU PT. Hukum kepailitan Indonesia masih berorientasi pada likuidasi berbasis formalitas procedural, berbeda dengan pendekatan Uni Eropa dan negara-negara common law yang menempatkan mekanisme penyelamatan dan rehabilitasi sebagai respons utama terhadap kesulitan likuiditas. Artikel ini berkontribusi pada penguatan argumentasi perlunya harmonisasi regulasi dan adopsi dual insolvency test untuk membedakan kesulitan likuiditas dari insolvabilitas struktural, serta guna melembagakan mekanisme penyelamatan dan jalur rehabilitasi sebagai prioritas sebelum likuidasi dalam hukum kepailitan di Indonesia.